Application of persuasive systems design principles to design a self-management application user interface for Hispanic informal dementia caregivers: user preferences and perceptions. Issue 1 (11th February 2022) - Lucero, Robert J; Yoon, Sunmoo; Suero-Tejeda, Niurka; Arcia, Adriana; Iribarren, Sarah; Mittelman, Mary; Luchsinger, Jose; Bakken, Suzanne
Abstract: Objective: We designed an mHealth application (app) user interface (UI) prototype informed by participatory design sessions, persuasive systems design (PSD) principles, and Lorig and Holman's self-management behavior framework to support self-management activities of Hispanic informal dementia caregivers and assessed their perceptions and preferences regarding features and functions of the app. Materials and Methods: Our observational usability study design employed qualitative methods and forced choice preference assessments to identify: (1) the relationship between user preferences for UI features and functions and PSD principles and (2) user preferences for UI design features and functions and app functionality. We evaluated 16 pairs of mHealth app UI prototype designs. Eight paper-based paired designs were used to assess the relationship between PSD principles and caregiver preferences for UI features and functions to support self-management. An Apple iPad WIFI 32GB was used to display another 8 paired designs and assess caregiver preferences for UI functions to support the self-management process. Results: Caregivers preferred an app UI with features and functions that incorporated a greater number of PSD principles and included an infographic to facilitate self-management. Moreover, caregivers preferred a design that did not depend on manual data entry, opting instead for functions such as drop-down list, drag-and-drop, and voice query to prioritize, choose, decide, and search when performing self-management activities. Conclusion: Our assessment approaches allowed us to discern which UI features, functions, and designs caregivers preferred. The targeted application of PSD principles in UI designs holds promise for supporting personalized problem identification, goal setting, decision-making, and action planning as strategies for improving caregiver self-management confidence. Lay Summary: Informed by a set of persuasive systems design principles, we designed an mHealth application (app) user interface prototype to support self-management activities of Hispanic informal dementia caregivers and assessed their perceptions and preferences regarding the app user interface and functionality. We asked 14 Hispanic informal dementia caregivers about their perceptions and preferences for 16 paired user interface designs; 8 using paper-based and 8 on an iPad. We also asked them about preferred app functionality. Caregivers preferred an app user interface with features and functions that included more persuasive systems design principles and an infographic to help with self-management. They also preferred functions like drop-down list, drag-and-drop, and voice query for data entry when documenting self-management activities. Caregiver's perceptions and preferences suggest that use of persuasive systems design principles in user interface designs holds promise for supporting personalized problem identification, goal setting, decision-making, and action planning as strategies for improving caregiver self-management confidence.